2015
DOI: 10.1039/c5cp05388a
|View full text |Cite
|
Sign up to set email alerts
|

Internal conversion outcompetes autodetachment from resonances in the deprotonated tetracene anion continuum

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 90 publications
7
41
0
Order By: Relevance
“…This level of theory has previously proven reliable to determine resonance energetics in a range of conjugated and aromatic anions. 14,15,17,20,31 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This level of theory has previously proven reliable to determine resonance energetics in a range of conjugated and aromatic anions. 14,15,17,20,31 …”
Section: Methodsmentioning
confidence: 99%
“…The photoelectron spectra are dominated by a peak at low electron kinetic energy, eKE, which is generally indicative of the indirect electron loss process of thermionic emission. 15,20,28,29 In addition to this low eKE peak, there are several minor features at higher eKE. In the hν = 4.13 eV spectrum, the low eKE peak has a shoulder that extends up to ~1.4 eV and a weak feature that peaks at eKE ~ 2.5 eV as indicated by the asterisk in Figure 1(a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…All images were accumulated with a 500 ns MCP gate; systematic delay of the MCP gate in 50 ns steps relative to the light pulse showed that most electron ejection occurred on a < 50 ns timescale regardless of cluster size, suggesting that only a modest amount of thermionic emission occurred. 7,10,28,29 Photoelectron image reconstructions used a polar onion peeling 30 algorithm, providing photoelectron spectra and angular distributions (see ESI). The photoelectron eKE scale was calibrated from the spectrum of I -and the velocitymapping resolution is around 5%.…”
Section: Methodsmentioning
confidence: 99%